2021
DOI: 10.1021/acsbiomaterials.1c00509
|View full text |Cite
|
Sign up to set email alerts
|

Prefabricated 3D-Printed Tissue-Engineered Bone for Mandibular Reconstruction: A Preclinical Translational Study in Primate

Abstract: The advent of three dimensionally (3D) printed customized bone grafts using different biomaterials has enabled repairs of complex bone defects in various in vivo models. However, studies related to their clinical translations are truly limited. Herein, 3D printed poly(lactic- co -glycolic acid)/β-tricalcium phosphate (PLGA/TCP) and TCP scaffolds with or without recombinant bone morphogenetic protein −2 (rhBMP-2) coating were utilized to repair primate’s large-volume mandibular defects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Extensive studies demonstrate that in vivo new bone formation can be enhanced by loading growth factors (BMP-2 and TGF-β1) onto bone grafts. [61][62][63] As members of TGF-β superfamily, BMP-2 and TGF-β1 have the similar Smad signaling pathways. BMP2 activates the phosphorylation of Smad1/5/8 proteins, while, TGFβ1 triggers the phosphorylation of Smad2/3 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies demonstrate that in vivo new bone formation can be enhanced by loading growth factors (BMP-2 and TGF-β1) onto bone grafts. [61][62][63] As members of TGF-β superfamily, BMP-2 and TGF-β1 have the similar Smad signaling pathways. BMP2 activates the phosphorylation of Smad1/5/8 proteins, while, TGFβ1 triggers the phosphorylation of Smad2/3 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cumulative release of rh‐BMP‐2 from scaffolds has been assessed (48.5 ± 6.4% at the 21th day). [ 42 ] Nokhbatolfoghahaei et al have also tested β ‐TCP scaffolds in several conditions in a canine animal model, and always reported higher histomorphometry values of NB in the presence of rh‐BMP‐2 (NB = 48.443 ± 0.250%). [ 39 ] On the other hand, despite reporting a modest trend of bone formation for PCL/ β ‐TCP scaffolds soaked into a BMP‐2/collagen solution (BV/TV ≈ 13%), results of Lee et al lacked statistical significance when compared to the control group (PCL/ β ‐TCP alone).…”
Section: Bioactive Molecules For Mandibular Regenerationmentioning
confidence: 99%
“…[ 95 ] Cao et al showed the superiority of β ‐TCP scaffolds cultivated in the latissimus dorsi muscle of primates over a three‐month period. [ 42 ] Vascularization of the construct was improved due to penetration of host blood vessels from the neighboring muscle tissue and, after orthotopic transplantation in a mandibular defect, pronounced effects of bone regeneration were shown (BV/TV ≈ 85% and NB ≈ 60%). Interestingly, PLGA/TCP composite scaffolds prefabricated in the same manner were resorbed too much and could not be used further.…”
Section: Vascularization Strategies For Mandibular Regenerationmentioning
confidence: 99%
“…Cao et al utilized a primate mandibular defect model to assess the effects of rhBMP-2 coating on their PLGA/TCP scaffold. Although in vitro cytoskeletal and nuclear staining of co-cultured hBMSCs found no significant difference between the two groups in cell proliferation and differentiation, the in vivo microCT analysis of bone volume/total volume revealed a significantly increased amount in the augmented group [ 216 ]. Lauer et al investigated 3D-printed porous PLA cylinders functionalized with either BMP-7 or stromal derived factor-1 (SDF-1) in critical-sized femoral rat defects, and found that scaffolds with BMP-7 conferred the most distinct effect on new bone formation, even compared to SDF-1.…”
Section: Future Directions For Addressing Bone Lossmentioning
confidence: 99%